Allelic polymorphisms of Malarial and human genes in relation to disease occurrence and pathogenesis - Perera, W. V. J. (University of Colombo, 1999)
Among the determinants of pathogenesis of malarial disease, parasite genetic factors and host genetics play a major role. Human TNF allele polymorphisms and their associations with severe infectious diseases and genetic composition of malarial infections were studied using PCR oligonucleotide probing. The results of this study showed that the mean number of genetically distinct parasite clones per isolate for parasite infections in Kataragama (endemic) patient population (2.17) is significantly higher than the parasite isolates from patients in Colombo (non endemic) (1.59=0.0001)
Faculty of Medicine, University of Colombo, 1999 Degree : Ph. D
Keywords: Malaria-genetics